"KAJIAN NILAI MARSHALL CAMPURAN SMA 0/11 DENGAN MENGGUNAKAN FLY ASH (ABU TERBANG) SEBAGAI PENGGANTI FILLER ABU BATU" - Ishak Ishak (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
One type of flexible pavements that have high structural value is SMA (Split Mastic Asphalt), so that high school is widely used in Indonesia to the streets with a high service level. SMA 0/11 (Split Mastic Asphalt 0/11) composed of aggregates of several factions that have a certain gradation using bitumen belt material.This study uses a SMA 0/11 with variations in fly ash content of 0%, 5%, 10%. SMA 0/11 mixture then compacted with a compaction temperature of 1600C. Then the test piece immersed in water bath with a temperature of 600C with a soaking time of 0.5 hours and 24 hours. Then testing by using Marshall.The addition levels of fly ash with a variation of 0%, 5%, 10%, greater stability of the value obtained with a value of 1665.135 kg, the value VITM getting down to the lowest value of 4.90%, the value of flow rose to a value of 4.644 mm, the value VFWA getting down to the value of 71.499%, the greater the density value with a value of 2.125 g / cm3 and Marshall Quotient higher value with a value of 354.323 kg / mm.Key words : SMA 0/11, fly ash, Marshall Test